Sex differences in muscle fatigue among competitive rowers during a 2000m time trial - Spagnuolo, P. L. (McGill University, 2023)
The goal of this master`s project was to examine sex differences in rowing-related fatigue, as well as muscle activation and oxygenation among competitive rowers. Varsity rowers with previous and current competition experience completed maximal voluntary muscle contractions followed by an all-out 2000m time trial on a Concept 2 rowing ergometer. These athletes are classified under the 3rd tier of sports participant classification framework (highly trained/national level)(McKay et al., 2022). Patterns of muscle activation, using surface electromyography (EMG), and quadriceps (vastus lateralis) muscle oxygenation, using near infrared spectroscopy (NIRS), were measured continuously throughout the row. Five strokes were averaged at 7 fixed distances to assess how these measures progressed with fatigue. The EMG root mean square (RMS) of middle trapezius, biceps brachii, rectus femoris, lumbar and thoracic erector spinae muscles all saw significant decreases throughout the trial in females, but not in males. Females also had significantly greater initial muscle activation from the start of the trial compared to males for biceps brachii, vastus lateralis, and rectus femoris. Additionally, females maintained a greater oxygenation level in vastus lateralis compared to males. This observation, combined with females demonstrating significantly greater heart rates compared to males throughout the trial, would suggest that females rely on the cardiovascular system significantly more than males to complete the row. These results are likely caused by greater type I muscle fibers within the vastus lateralis for females. Fiber type disparity could offer an explanation as to why females are experiencing exhaustion in certain muscle groups while males are not. The results from this study can help identify differences between male and female rowers and create the foundation for future studies to adapt training and decrease risk of injury